How do social innovations contribute to growth-independent territorial development? Case studies from a Swiss mountain region - Mayer, Heike; Tschumi, Pascal; Perren, Romario; Seidl, Irmi; Winiger, Andrea; Wirth, Samuel (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
In this article we investigate the role of social innovations in territorial development. More specifically we examine the ways in which social innovations can contribute to growth-independent local and regional development. By growth-independent territorial development we understand the ways in which a society, including its economy and its institutions, can continue to fulfill its functions such as providing public services, while not being existentially dependent on economic growth. Growth independence is a precondition for a post-growth society. Based on case studies of social innovations in the Bernese Oberland (Switzerland), this article shows that the examined social innovations can contribute to economic growth independence through entrepreneurial decisions that foster (re-)localization, de-commercialization, low capital intensity, and self-governance. These decisions help make the social innovation initiatives growth-independent and hence they contribute to a post-growth society. Our research adds to the literature on the role of social innovation for a post-growth society and clarifies the role of socially innovative initiatives in territorial development.